Glioma Cells With Genetically Engineered IGF-I Receptor Downregulation Can Persist in the Brain in a Dormant State - Samani, Amir A.; Nalbantoglu, Josephine; Brodt, Pnina (Frontiers in Oncology, 2020)
Glioblastoma multiforme is an aggressive malignancy, resistant to standard treatment modalities and associated with poor prognosis. We analyzed the role of the IGF system in intracerebral glioma growth using human and rat glioma cells. The glioma cells C6 and U87MG were transduced with a genetically engineered retrovirus expressing type 1 insulin-like growth factor (IGF-IR) antisense RNA, either before or after intra-cerebral implantation of the cells into Sprague Dawley rats or nude mice, respectively and tumor growth and animal survival were monitored. Rat glioma cells transduced prior to orthotopic, intra-cerebral implantation had a significantly increased apoptotic rate in vivo and a significantly reduced tumor volume as seen 24 days post implantation (p < 0.0015). This resulted in increased survival, as greater than 70% of the rats were still alive 182 days after tumor implantation (p < 0.01), as compared to 80% mortality by day 24 in the control group. Histomorphology and histochemical studies performed on brain tissue that was obtained from rats that survived for 182 days revealed numerous single cells that were widely disseminated throughout the brain. These cells expressed the β-galactosidase marker protein, but were Ki67negative, suggesting that they acquired a dormant phenotype. Direct targeting of the C6 cells with retroviral particles in vivo was effective and reduced tumor volumes by 22% relative to controls. A significant effect on tumor growth was also seen with human glioma U87MG cells that were virally transduced and implanted intra-cerebrally in nude mice. We observed in these mice a significant reduction in tumor volumes and 70% of the animals were still alive 6 months after tumor implantation, as compared to 100% mortality in the control group by day 63. Our results show that IGF-IR targeting can inhibit the intracerebral growth of glioma cells. They also suggest that IGF-IR expression levels may determine a delicate balance between glioma cell growth, death and the acquisition of a dormant state in the brain.